AUDIT SYARIAH PADA LEMBAGA KEUANGAN SYARIAH GUNA MEWUJUDKAN GOOD CORPORATE GOVERNANCE (STUDI MULTI SITUS PADA BAITUL MAAL WAT TAMWIL DI TULUNGAGUNG DAN BANK PEMBIAYAAN RAKYAT SYARIAH DI KEDIRI) - Dyah Pravitasari (Nurul Jadid University, 2019)
Sharia financial institutions have significantly develop. This requires that sharia finance institutions continue to grow and improve their services for the higher level of community confidence. For the institution to run well, free of fraud and citting, it is necessary to do check or audit. Audit to be conducted is an internal audit and sharia audit. The position of the audit activities relates to the compliance test or the adherence to the Sharia accounting principles and in accordance with the AAOFI’s standar. The aims of the audit is to realize the good corporate governance more better.